2017
DOI: 10.1016/j.ajhg.2017.06.006
|View full text |Cite
|
Sign up to set email alerts
|

REST Final-Exon-Truncating Mutations Cause Hereditary Gingival Fibromatosis

Abstract: Hereditary gingival fibromatosis (HGF) is the most common genetic form of gingival fibromatosis that develops as a slowly progressive, benign, localized or generalized enlargement of keratinized gingiva. HGF is a genetically heterogeneous disorder and can be transmitted either as an autosomal-dominant or autosomal-recessive trait or appear sporadically. To date, four loci (2p22.1, 2p23.3-p22.3, 5q13-q22, and 11p15) have been mapped to autosomes and one gene (SOS1) has been associated with the HGF trait observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 42 publications
5
57
0
Order By: Relevance
“…The more moderate phenotype, classical MFS, is caused by nonsense mutations that activate the NMD RNA surveillance pathway, thereby degrading mutant transcripts and resulting in FBN1 haploinsufficiency. The data support the concept of distinct pathogenetic mechanisms, GoF versus LoF (BAYRAM et al . 2017; COBAN-AKDEMIR et al .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The more moderate phenotype, classical MFS, is caused by nonsense mutations that activate the NMD RNA surveillance pathway, thereby degrading mutant transcripts and resulting in FBN1 haploinsufficiency. The data support the concept of distinct pathogenetic mechanisms, GoF versus LoF (BAYRAM et al . 2017; COBAN-AKDEMIR et al .…”
Section: Discussionsupporting
confidence: 87%
“…PTCs located in the final coding exon are specifically prone to escape NMD and so are processed distinctly from those in internal exons in terms of transcript degradation, leading to the stable translation of truncated proteins (BAYRAM et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Although mutations in the constitutively spliced exons of REST have been linked to cancer and gingival fibromatosis (Mahamdallie et al, 2015; Bayram et al, 2017), ours is the first study to associate REST with hearing loss, and DFNA27 is the first genetic variant shown to affect the alternative splicing of REST. The effects of the DFNA27 variant are highly unusual in that either gain or loss of function of the encoded protein occurs depending on the cellular context.…”
Section: Discussionmentioning
confidence: 82%
“…To unravel the genetic basis of HGF, past studies have mainly used linkage analysis, candidate gene approaches, and whole‐exome sequencing. As a result, chromosomes 2p21‐p22 ( GINGF ), 2p13‐p16, 2p22.3‐23 ( GINGF3 ), 5q13‐q22 ( GINGF2 ), 4q21, 4q, son of sevenless gene ( SOS1 ), and RE1‐silencing transcription factor ( REST ) have been associated with non‐syndromic HGF (Bayram, White, & Elcioglu, ; DeAngelo, Murphy, Claman, Kalmar, & Leblebicioglu, ; Sah, Chandra, & Kaur, ). However, these genetic methods have not fully revealed the mechanisms underlying idiopathic HGF.…”
Section: Introductionmentioning
confidence: 99%